If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 2p + -3p = 0 Combine like terms: 5p + 2p = 7p 7p + -3p = 0 Combine like terms: 7p + -3p = 4p 4p = 0 Solving 4p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Divide each side by '4'. p = 0 Simplifying p = 0
| -8+5x=3+7(x-1) | | Y-4=5y | | -7=3x | | -125=5(w-12) | | 15b-14a+5b+16a= | | 6(1-6x)=-25-5x | | 3(2y+5)=11 | | 14+d-6=7 | | Y-5=-(4-y) | | 12w=16(w-8) | | -75m=15 | | a^4+2a^2-3=0 | | -49=a+5 | | 5b+12=-5 | | -(6p+8)+4p=-1-p | | 64=2x+20 | | 4+4b=1 | | -7n-33=-8(8-3n) | | ln(x+6)=9 | | Hg(x)=2.87(24)sqrt+20.08 | | 4(2x-3)+x=9x-1-6x+19 | | 3p=-4p+7 | | -y+18=-32 | | 3r+3=-5 | | -5y+24=-1 | | n-21=-3(-4+7)+6n | | 7+4r=10 | | -3y-48=-7 | | 2.2=2n+0.2 | | 4y-35=-3 | | 55-10x=10x | | 5y-1=-11 |